Entrepreneurship, innovation and sustainable growth : theory, policy and practice - Asgary, Nader H.; Maccari, Emerson A.; Hollnagel, Heloisa C. (Routledge, 2024)
"Entrepreneurship and innovation play a vital role in fostering sustainable development. Advances in technology and communications have both transformed the process of business as well as strengthened the role of entrepreneurship in developed and developing countries. This new edition of Entrepreneurship, Innovation and Sustainable Growth provides the fundamental concepts and applications for faculty and students in this field, and also serves as a professional reference for practicing entrepreneurs and policymakers. Each chapter provides a clear guide to the conceptual and practical elements that characterize entrepreneurship and the process of new venture formation, including functional strategies in key areas such as marketing, information technology, human resources management, and accounting and finance. Updated throughout to take account of recent developments in topics such as environmental impacts, diversity and inclusion, and COVID-19, the book is a comprehensive and holistic approach to the theory, policy and practice of entrepreneurship and innovation. Keeping practicality as the book's core aim, all chapters include a long case study to set the scene and then draw upon shorter cases from both developing and developed countries to reinforce key learning objectives and the real-world application of the book's core concepts. With new questions and exercises presented throughout in order to encourage discussion and problem-solving, quick summaries of the important concepts and definitions, and extensive support for lecturers and students, Entrepreneurship, Innovation and Sustainable Growth, Second Edition, is ideal for students at undergraduate and postgraduate level"-- Provided by publisher.
Revised edition of Entrepreneurship, innovation and sustainable growth, 2020.
Keywords: Entrepreneurship.; Sustainable development.; Technological innovations -- Economic aspects.; elektronické knihy; electronic books